2012
DOI: 10.3109/17453674.2012.702392
|View full text |Cite
|
Sign up to set email alerts
|

5-year clinical and radiostereometric analysis (RSA) follow-up of 39 CUT femoral neck total hip prostheses in young osteoarthritis patients

Abstract: Background As the number of young patients receiving total hip arthroplasty increases, bone-saving implantations facilitating possible future revision, such as the CUT femoral neck prosthesis, are gaining importance. There have been few medium-term results reported for this prosthesis, however, and its migration pattern has not been analyzed.Patients and methods 39 consecutive CUT femoral neck prostheses were implanted in 32 patients, mean age 37 (17–58) years, with symptomatic osteoarthritis and either less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
0
17
0
4
Order By: Relevance
“…Bone quality is a key parameter to achieve rigid press fit fixation with a metaphyseal stem (99,221,222). We found that the short stem used in study IV was not as forgiving as a conventional stem regarding surgical technique and that correct implant sizing is mandatory to achieve good fixation.…”
Section: Implant Migrationmentioning
confidence: 89%
“…Bone quality is a key parameter to achieve rigid press fit fixation with a metaphyseal stem (99,221,222). We found that the short stem used in study IV was not as forgiving as a conventional stem regarding surgical technique and that correct implant sizing is mandatory to achieve good fixation.…”
Section: Implant Migrationmentioning
confidence: 89%
“…Sta łe do sko na le nie pro tez sto so wa nych w cał kowi tej alo pla sty ce sta wu bio dro we go po wo du je, że wy ko ny wa nie tych ope ra cji mo żli we jest u co raz młod szych i bar dziej ak tyw nych pa cjen tów, bę dą cych w wie ku pro duk cyj nym [1][2][3]. Mi mo że do pro te zo plasty ki sta wu bio dro we go kwa li fi ko wa ne są głów nie oso by star sze, to np.…”
Section: Wstępunclassified
“…El índice de masa corporal promedio del grupo fue 27 (rango [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. El diagnóstico primario fue artrosis primaria (82 casos), displasia del desarrollo (6 casos), osteonecrosis (8 casos), condrólisis idiopática (2 casos), secuela de enfermedad de Perthes (1 caso) y sinovitis vellonodular pigmentada (1 caso).…”
Section: Materiales Y Métodosunclassified
“…[4][5][6][7][8][9][10] Kendoff y cols. 11 y otros autores [12][13][14][15][16][17][18][19][20][21][22][23][24] han publicado un 99% de supervivencia de la prótesis en 1394 casos con un seguimiento promedio de seis años usando el diseño CFP (Waldemar Link GmbH, Hamburgo, Alemania). Hay escasos informes publicados sobre los resultados con el tallo MiniHip TM (Corin, Cirencester, Reino Unido): 3,25 una sola serie de pacientes operados por un equipo quirúrgico independiente de los diseñadores.…”
Section: Introductionunclassified